THE OSMOTIC BEHAVIOR OF ROD PHOTORECEPTOR OUTER SEGMENT DISCS - Heller, Joram (The Rockefeller University Press, 1971)
The permeability properties of frog rod photoreceptor outer segment discs were investigated in preparations of purified, dark-adapted, outer segment fragments by the techniques of direct volume measurement and electron microscopy. Outer segment discs were found to swell and contract reversibly in response to changes in the osmotic pressure of the bathing medium in accordance with the Boyle-van't Hoff law. By use of the criterion of reversible osmotic swelling, the disc membrane is impermeable to Na(+), K(+), Mg(+2), Ca(+2), Cl(-), and (PO(4))(-3) ions, whereas it is freely permeable to ammonium acetate. The disc membrane is impermeable to sucrose, although its osmotic behavior towards this substance is different from its behavior towards impermeable ions. Electron microscopy showed that the osmotic effects on the rod outer segment fragments represent changes in the intradiscal volume. Fixation with glutaraldehyde did not abolish the permeability properties of the disc membrane, and fixed membranes were still capable of osmotic volume changes. It is concluded from this study that the frog's rod photoreceptor outer segment discs are free-floating membranous organelles with an inside space separate and distinct from the photoreceptor intracellular space.